The Effect of Work Motivation Toward Employee Performance at PT. Permodalan Nasional Madani (Persero) Jakarta - Aldi Khairy Rusli; Hani Gita Ayuningtias (Jurnal Ilmu Sosial Politik dan Humaniora (JISORA), 2020)
Work motivation can be seen from the data and employee attendance employee delays the data in the company, judging by the attendance of data and delays the data of employees of PT. Permodalan Nasional Madani (Persero). From the Data Obtained can be said that the attendance and delay of employees of PT. Permodalan Nasional Madani (Persero) is fairlygood in every month. As for measuring the performance of employees in this research, they have a Key Performance Indicator and, preliminary questionnaire. This research aims to know the condition of intrinsic motivation and extrinsic motivation PT. Permodalan Nasional Madani (Persero) Jakarta as well as influence the intrinsic motivation and extrinsic motivation to the employee performance. The approach to this research is quantitative with the type of descriptive research using IBM SPSS 20. While the method of analysis used is multiple linear regression. Method of collecting the data through the dissemination of questionnaires using sample 272 employees. The sampling method uses probability sampling technique while sampling technique uses simple random sampling. The results of the study proved that the motivation of intrinsic partially work has a significant influence on employee performance, while the extrinsic motivation of work has no significant influence on the employee's performance. Also the results proved that the motivation of intrinsic work and motivation of extrinsic work have a simultaneous influence on the employee's performance. It is hoped that Researchers can then use other variables such as organizational culture, job satisfaction, and employee commitment. To know other aspects not addressed in this research and can also use other research methods such as path analysis and SEM analysis. Advice for companies to provide creativity training that aims to provide opportunities for its employees to bring out the idea of ​​the free as rational as possible.